Do we need ‘new’ omega-3 polyunsaturated fatty acids formulations? - CICERO, ARRIGO FRANCESCO GIUSEPPE; BORGHI, CLAUDIO (Expert Opinion on Pharmacotherapy, 2015)
The therapeutic value of omega-3 polyunsaturated fatty acids (PUFAs), mainly (but not only) found in fish oils, eicosapentaenoic and docosahexaenoic acids (EPA and DHA, respectively), has been extensively studied in a wide variety of disease conditions, predominantly in cardiovascular disease. However, the significant difference in efficacy observed in various conditions with different dosages seems to be at least partly related to the large discrepancy in quality of the product and to the bioavailability of the omega-3 PUFA. The research of new sources (e.g., from arctic Krill oil) and pharmaceutical forms of omega-3 PUFA (e.g., omega-3 carboxylic acids) is needed in order to detect the one with the best bioavailability and efficacy, and with a parallel reduction in the production costs. There is also the need to understand if long-term PUFA supplementation could increase the efficacy of the alreadyavailable evidence--based therapies for cardiovascular disease prevention and for the management of the diseases where the use of PUFA could have a possible improving effect.